XC roller skiing on a force measuring treadmill - Kehler, A. L.; Hajkova, E.; Holmberg, H. C.; Kram, R. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Although the kinematics (e.g. stride length, joint angles, etc.) of cross country (XC) skiing have been extensively studied, only a few studies have measured the forces involved (e.g.1,3,4,5). Force measuring treadmills (FTM) have catalyzed the study of walking and running biomechanics, but to our knowledge have not been utilized to study XC skiing. Thus, we investigated the feasibility of using a FTM to better understand the fundamental biomechanics of diagonal stride XC skiing (DIA). We recorded the perpendicular (Fperp) and parallel (Fpar) forces exerted on the FTM during DIA at multiple speeds and inclines. We hypothesized that both forces would increase at faster speeds and up steeper inclines.